Allergen Arrays: Click‐Chemistry Based Allergen Arrays Generated by Polymer Pen Lithography for Mast Cell Activation Studies (Small 38/2016). Issue 38 (October 2016) - Kumar, Ravi; Bonicelli, Alice; Sekula‐Neuner, Sylwia; Cato, Andrew C. B.; Hirtz, Michael; Fuchs, Harald
Abstract : Microfluidic encapsulated allergen arrays are created by M. Hirtz and co‐workers on page 5330 using polymer pen lithography (PPL). These arrays are utilized in mast cell activation studies on a single cell level. The overall setup enables easy handling of cell suspension, incubation, and read‐out by fluorescence microscopy, allowing immune cell activation screening to be easily adapted for diagnostics and biomedical research.